Analisis Praktik Corporate Social Responsibility (CSR) Saat Pandemi Covid-19 pada Perusahaan Farmasi - Liza Wahyuni; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze: 1) the level and quality of Corporate Social Responsibility (CSR) disclosure during the Covid-19 in pharmaceutical companies based on the 2021 GRI Standards, 2) Corporate Social Responsibility (CSR) practiced by pharmaceutical companies in helping to overcome the Covid-19 based on the 2021 GRI Standards. This research is a qualitative research using content analysis methods. The research was conducted on pharmaceutical sector companies in Indonesia by taking 4 samples of companies, namely PT Indofarma Tbk, PT Kalbe Farma Tbk, PT Phapros Tbk, and PT Sido Muncul Tbk. The data used is data for 2019-2020 when the Covid-19 entered Indonesia. The research data comes from the company's sustainability report. The results of content analysis show that the Covid-19 has played a major role in the disclosure of Corporate Social Responsibility (CSR) in the pharmaceutical sector. Two of the four companies that were the subject of the study had quite high Corporate Social Responsibility (CSR) disclosures, namely PT Kalbe Farma and PT Sido Muncul Tbk. Four companies that are active research subjects provide assistance in the form of donations to the community in efforts to tackle the Covid-19.